Public Science, Public Access. - David Flaxbart (Issues in Science and Technology Librarianship)
This article comments on the introduction of the Federal Research Public Access Act of 2006 in the U.S. Senate. This bill would require most recipients of federal research funds to make their findings freely available within six months of publication. The position of the publishing industry on the bill is cited. In addition, this article presents the concerns of the scientific community on the bill.